Tularemia as a cause of cervical lymphadenitis - Ahmet Eyibilen (Dicle Medical Journal, 2011)
The etiology of cervical lymphadenitis may be related to the many different reasons. It is stated that tularemia is a rare cause of cervical lymphadenitis. However, tularemia is seen as endemic in several regions in our country. Tularemia outbreaks have been reported recently. Tokat and surrounding area are the places where tularemia is seen as endemic. In this paper, seven patients with cervical lymphadenitis due to tularemia between 2007 and 2008 are presented. The aim of this paper is to emphasize that tularemia is an increasing cause of cervical lymphadenitis in our region although it is not described as a common reason for cervical lymphadenitis.